MODEL OF INTERNAL QUALITY ASSURANCE SYSTEM (SPMI) IN STKIP SINGKAWANG - Mursidi, Andi; soeharto, soeharto; setyowati, rini; ting, i-hsien; Sundiman, Didi; Sabran, Sabran (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2018)
This study aims to determine the model of the Internal Quality Assurance System applied in STKIP Singkawang. This study is a qualitative research using case study as a research method. The study was conducted in STKIP Singkawang with research subjects STKIP Singkawang Quality Assurance Agency. The technique is done to collect data consist of interviews and observations. The results showed (1) an internal quality assurance system STKIP Singkawang applying standard 41; and 2) quality assurance management model applied in STKIP Singkawang is PDCA model consisting of four main components, namely Plan, Do, Check and Action.